Editorial Preface - Riyani, Irma (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2021)
Welcome to the current publication of Wawasan: Journal of Religious and Socio-Cultural Studies. It is a great challenge to publish high-quality manuscripts for Volume 6, No. 2, 2021. Wawasan is a peer-reviewed, open-access journal and free of charge to the authors dedicated to publishing articles and facilitating widespread dissemination and impact on the field. Pandemic Covid-19 should not prevent us from conducting high-quality research and disseminating the findings in a form of an article journal. Wawasan journal team members are dedicated to continuing support for providing open access and receiving articles for publications. In this issue, readers will find a diverse group of manuscripts and have something new and useful–and sometimes surprising–to say about a wide range of religious studies. Most of the articles in this volume are the result of the 3rd conference on Islamic and Socio-Cultural Studies (CISS) that we organised on November 17 to 18, 2021. We have very stimulating seven articles focused on religious and cultural studies. Dawam Multazami et.al. is investigating the interest pool of hashtag #IslamNusantara that spark hot debate in 2017 since promoted officially by one of the prominent Islamic organisation, Nahdlatul Ulama. The second article by M Naufal Waliyudin et. al. is discussing the experience of youth in the interfaith organisation to create the youth as an agent of peace and harmony in Indonesia. Santi Paramithan et.al. brought us to understand the content of the verse Tanha Vagga of the Dhammapada scripture through semantic analysis. The issue of radicalism is still around us and the article by Dzuriyatun Toyibah shows us the household arrangement of the terrorists convicted life. This article argues that the position of women, as wives and mothers, shows significance in deradicalising the family. The Balinese Hindu arts show not only interesting but also sacred. Abdullah Fuadi investigates these arts to prove their sacredness and challenge Hegel’s theory of ‘the death of arts.’ Meanwhile, the two last articles identify the kitab written by prominent ulama in pesantren in Bandung and presented historically by Zulkarnain Yani. Its finding is important to show the Islamic scientific traditions and network of the ulama in pesantren in Bandung. The article by Puji Sulani et.al. investigates the sustainability of cultural identity held by the ex-adherents of Kawula Warga Naluri in Banjarnegara, Central Java. The ex-adherent struggle between keeping their cultural identity and government regulation to adhere to one of the state official religions. As you read throughout this volume of Wawasan journal, I would like to remind you that the success of our journal depends directly on the number of quality articles submitted for review. Accordingly, I would like to request your participation by submitting quality manuscripts for review. As the Editor-in-Chief of this journal, I would like to extend my gratitude to the Dean of the Faculty of Ushuluddin for continuous support in scientific publication, my managing editor, editorial board members, and reviewers for creating this issue. Most importantly, I am deeply grateful to all the authors for their excellent works and remarkable contributions.